1999
DOI: 10.1046/j.1365-2826.1999.00300.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Stressor Controllability on Stress‐Induced Neuropeptide mRNA Expression within the Paraventricular Nucleus of the Hypothalamus

Abstract: Many stressors elicit changes in corticotrophin (CRH), enkephalin (ENK), and neurotensin (NT) mRNA levels within the medial parvocellular region of the paraventricular nucleus of the hypothalamus (mpPVN), and the pattern of changes in mRNA levels appears to depend on the physical characteristics of the stressor. We questioned whether psychologically distinct stressors would cause different patterns of neuropeptide mRNA expression within the PVN. Psychologically distinct stressors were created by employing a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 64 publications
0
33
1
Order By: Relevance
“…Even though ES may condition less fear to the wheel turn apparatus than does IS, it still conditions some fear (Mineka and Hendersen, 1985), certainly not "negative fear". The present results are quite striking because ES exposes the subject to very aversive stimulation and is highly "stressful" as indicated by an asymptotic HPA axis response to ES (Maier et al, 1986;Helmreich et al, 1999), yet it reduced later fear conditioning. In addition, exposure to ES after fear conditioning facilitated the reduction of fear responses during extinction and eliminated spontaneous recovery of fear.…”
Section: Discussionmentioning
confidence: 64%
“…Even though ES may condition less fear to the wheel turn apparatus than does IS, it still conditions some fear (Mineka and Hendersen, 1985), certainly not "negative fear". The present results are quite striking because ES exposes the subject to very aversive stimulation and is highly "stressful" as indicated by an asymptotic HPA axis response to ES (Maier et al, 1986;Helmreich et al, 1999), yet it reduced later fear conditioning. In addition, exposure to ES after fear conditioning facilitated the reduction of fear responses during extinction and eliminated spontaneous recovery of fear.…”
Section: Discussionmentioning
confidence: 64%
“…Lastly, studies from a variety of labs have reported variable results when examining acute stress effects on CeA CRF mRNA levels. Our lab and others have shown that restraint stress and psychological stress can increase CeA CRF mRNA levels, whereas other studies have failed to demonstrate a change in CeA CRF mRNA (Helmreich et al, 1999), including a study published from our laboratory (Herringa et al, 2004). These studies suggest that the effects of acute stress on amygdala CRF mRNA are variable and may be dependent on context associated cues and the type of stressor used as well as other factors such as the rat strain used.…”
Section: Discussionmentioning
confidence: 66%
“…Central administration of neurotensin was reported to increase plasma levels of ACTH and corticosterone (Gudelsky et al, 1989;Nicot et al, 1994;Nicot et al, 1997). Psychological stressors, such as non-escapable tail electric shock in rats, were found to increase neurotensin mRNA within the medial parvocellular region of the paraventricular nucleus of the hypothalamus (Helmreich et al, 1999). Neurotensin receptor blockade by the non-peptide neurotensin NT 1 receptor antagonist SR48692 was found to attenuate restraint stress-induced elevations in hypothalamic pituitary adrenal activity , but it was without effect in a variety of different classical animal models of anxiety in rodents (Griebel et al, 2001a).…”
Section: Effect Of the Neurotensin Receptor Antagonist Sr48692 In Thementioning
confidence: 98%